Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - XIV. (Coleoptera: Dytiscidae, Haliplidae, Gyrinidae, Rhysodidae, Paussidae). - Döbler, Helga (Contributions to Entomology = Beiträge zur Entomologie, 1976)
The types of the families Dytiscidae, Haliplidae, Gyrinidae, Rhysodidae and Paussidae of Coleoptera preserved in the collections of the Department of Taxonomy of Insects of the Institute of Plant Protection Research of the Academy of Agricultural Sciences of the GDR are listed. Their first descriptions are quoted and data on the existing type material are given.